Influence of Gold Nanoparticles on the Luminescence of an Acrylated Isocyanonaphthalene Derivative - J. Burunkova; S. Keki; A. Veniaminov; M. Nagy; L. Daroczi; S. Kokenyesi (Advances in Condensed Matter Physics)
Dodecanethiol-functionalized gold nanoparticles were incorporated into the polymer matrix of diurethane-methacrylate monomer mixture in the presence of SiO2 nanoparticles (8 wt %) and a new reactive organic luminescent material ACAIN (1-N-(2-acryloyloxy-3-chloroprop-1-yl)-amino-5-isocyanonaphthalene, 1 wt %). This way, a new, probably multifunctional, polymer nanocomposite was obtained. It was shown that the addition of SiO2 nanoparticles enhances the fluorescent intensity of ACAIN by 1.5 times in the 450-550 nm spectral range. Furthermore, an additional fluorescence enhancement up to 4.5 times was observed when Au nanoparticles were added to this nanocomposite in a rather low (0.12 wt %) concentration.